Synthesis and Photoinduced Electron-Transfer Reactions in a La2@Ih-C80–Phenoxazine Conjugate - Akasaka, Takeshi; Nakata, Akira; Rudolf, Marc; Wang, Wei-Wei; Yamada, Michio; Suzuki, Mitsuaki; Maeda, Yutaka; Aoyama, Ryo; Tsuchiya, Takahiro; Nagase, Shigeru; Guldi, Dirk Michael (ChemPlusChem, 2017)
A newly designed electron donor–acceptor conjugate consisting of an endohedral dimetallofullerene (La2@Ih-C80) and phenoxazine (POZ) was successfully synthesized under Prato conditions. Our results document that the 1,3-dipolar cycloaddition took place across the [5,6] junction to afford exclusively the corresponding [5,6] cycloadduct. The structure of the conjugate was characterized by means of NMR spectroscopy, absorption spectroscopy, and electrochemical studies. Computational calculations suggest that the electron density of the highest occupied molecular orbital (HOMO) is distributed on the POZ moiety, whereas that of the lowest unoccupied molecular orbital (LUMO) is located at the endohedral La atoms, leading to efficient separation of the HOMO and LUMO in the conjugate. Time-resolved absorption spectroscopic investigations and spectroelectrochemical measurements corroborate the formation of the energetically low-lying (La2@Ih-C80).−–(POZ).+ radical-ion-pair state by means of ultrafast through-space electron transfer.
CRIS-Team Scopus Importer:2022-04-14
Keywords: donor–acceptor systems; electrochemistry; electron transfer; fullerenes; photochemistry